Tectonic evolution of the southern margin of the Amazonian craton in the late Mesoproterozoic based on field relationships and zircon U-Pb geochronology - Rizzotto, G.; Hartmann, L.; Santos, J.; McNaughton, Neal (Academia Brasileira de Ciencias, 2014)
New U-Pb zircon geochronological data integrated with field relationships and an airborne geophysical survey suggest that the Nova Brasilândia and Aguapeí belts are part of the same monocyclic, metaigneous and metasedimentary belt formed in the late Mesoproterozoic (1150 Ma-1110 Ma). This geological history is very similar to the within-plate origin of the Sunsás belt, in eastern Bolivia. Thus, we propose that the Nova Brasilândia, Aguapeí and Sunsás belts represent a unique geotectonic unit (here termed the Western Amazon belt) that became amalgamated at the end of the Mesoproterozoic and originated through the reactivation of a paleo-suture (Guaporé suture zone) in an intracontinental rift environment. Therefore, its geological history involves a short, complete Wilson cycle of ca. 40 Ma. Globally, this tectonic evolution may be related with the final breakup of the supercontinent Columbia. Mafic rocks and trondhjemites in the northernmost portion of the belt yielded U-Pb zircon ages ca. 1110 Ma, which dates the high-grade metamorphism and the closure of the rift. This indicates that the breakup of supercontinent Columbia was followed in short sequence by the assembly of supercontinent Rodinia at ca. 1.1-1.0 Ga and that the Western Amazon belt was formed during the accretion of the Arequipa-Antofalla basement to the Amazonian craton.